Case report: A case of metastatic BRAFV600-mutated melanoma with heart failure treated with immune checkpoint inhibitors and BRAF/MEK inhibitors - Nishizawa, Aya; Kawakami, Misaki; Kitahara, Yasuyuki (Frontiers in Oncology, 2024)
Background Novel therapies, immune checkpoint inhibitors (ICIs), and BRAF/MEK inhibitors (BRAFi/MEKi) provide unprecedented survival benefits for patients with advanced melanoma. However, the management of drug-induced adverse events is problematic for both agents and, although rare, can cause serious cardiac dysfunction. Case report A 42-year-old male patient with no significant medical history noticed a fading dark brown patch on his left anterior chest, which had been there for 20 years, after his second coronavirus disease 2019 (COVID-19) vaccination. The left axillary lymph node became swollen one week after a third booster vaccination. Thinking of it as an adverse reaction to the vaccine, but the swelling increased, so he visited a hospital. The patient presented with a brown macule with depigmentation on the left anterior chest and a 13 cm left axillary mass. A biopsy of the axillary mass showed a metastatic malignant melanoma. Positron emission tomography (PET) showed an accumulation only in the axillary lymph nodes. One month after the initial diagnosis, the axillary mass had further enlarged. In addition, pleural effusion, ascites, difficulty breathing, and systemic edema appeared, and he was diagnosed with heart failure (NYHA class III). Echocardiography showed an ejection fraction of 52% and electrocardiogram (ECG) showed no abnormal findings. Though it was (a life-threatening instead of the life-threatening) the life-threatening condition, we determined that the symptoms were associated with the current disease. Then nivolumab (nivo) plus ipilimumab (ipi) was initiated after explaining the risk of cardiac dysfunction associated with drug use to the patient. After initiation of ICIs, treatment was switched to BRAFi/MEKi (encorafenib/vinimetinib) after the patient tested positive for BRAF V600E. After one month of treatment, the tumor shrank significantly and achieved a complete remission after four months. Furthermore, as the tumor shrank, the patient’s heart failure improved, and he was able to continue treatment without serious drug-induced cardiotoxicity. Conclusion Both ICI and BRAFi/MEKi carry a risk of cardiac dysfunction. However, without any underlying cardiac disease or severe cardiac dysfunction, their administration should not necessarily be excluded if careful follow-up is provided.